2018
DOI: 10.2139/ssrn.3102280
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Mobility in the 19th Century: Micro-Level Evidence from the City of Zurich

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Favre et al (2018) showed similar results for 19 th -century Zurich, where rapid growth, industrialisation and institutional changes did not increase the levels of intergenerational social mobility.…”
supporting
confidence: 61%
“…Favre et al (2018) showed similar results for 19 th -century Zurich, where rapid growth, industrialisation and institutional changes did not increase the levels of intergenerational social mobility.…”
supporting
confidence: 61%
“…Data Source The data originate from the same twenty-five editions of the directory of citizens of the city of Zurich between 1799 and 1926 as described in Favre et al (2018). This source contains the universe of Zurich's adult male citizenry.…”
Section: Data and Descriptivesmentioning
confidence: 99%
“…Classifications of Occupations I employ the same set of occupational classifications as described in Favre et al (2018). For the main part of the analysis, I divide occupations into low, middle, and high socioeconomic positions (SEP).…”
Section: Data and Descriptivesmentioning
confidence: 99%
See 1 more Smart Citation